ANALYSIS OF ACCESS TO HEALTH SERVICE FACILITIES IN HOSPITALS FOR PERSONS WITH DISABILITIES IN MEDAN CITY: ANALISIS AKSES FASILITAS PELAYANAN KESEHATAN DI RUMAH SAKIT BAGI PENYANDANG DISABILITAS DI KOTA MEDAN - Ramadha Yanti Parinduri (UPMI Proceeding Series, 2023)
The purpose of this research is to find out how access to hospital services is for people with disabilities in Medan City and to find out the hospital's strategy in fulfilling the rights of people with disabilities in accessing services. The research method uses a qualitative approach. The collection technique used is a literature review. And the results of this research show that access to health services for people with disabilities at Medan City Hospital is not optimal. It is known that access to transportation is also a form of health facility service that has not yet been implemented in Medan City specifically for people with disabilities. This kind of access greatly influences the level of health services for people with disabilities to access the services of the target hospital. Mitra Medika Amplas and Mitra Sejati Hospitals are health service facilities that still do not provide access to health services for people with disabilities according to their needs.